EFEKTIVITAS MEDIA KOMIK DIGITAL DALAM PEMBELAJARAN MEMBACA CERITA PENDEK - Barliani, Karina; Kuswari, Usep; Koswara, Dedi (Jurnal Semantik, 2025)
Digital comic media is used as learning media that is tested in learning to read short stories. The aim is to test the effectiveness of digital comic media in learning to read short stories. The approach used is quantitative with experimental methods. The research data is the students' ability to read short stories. The research technique is test technique with instruments in the form of test questions. The results showed 1) the ability to read short stories of experimental class students after using digital comic media became 94.29 with very high criteria; 2) the ability to read short stories of control class students after learning without using digital comic media became 81.14 with high criteria; 3) the results of the t-test analysis showed the tcount value of 2.969, the ttable value of 1.691 and sig. (2tailed) is 0.004. The value of tcount> ttable, namely 2.969> 1.691 while the sig value (2tailed) is 0.004 < 0.05. So, it can be concluded that digital comic media effectively improves the ability of students in class XI TKJ SMKN Manonjaya in learning to read short stories.